Effective teaching, effective learning : making the personality connection in your classroom - Fairhurst, Alice M., 1936- (Davies-Black, 1995)
Understanding the role of personality in education. Teachers, teaching philosophy, and teaching style. Students and learning style. Making the personality connection.